ŚWIADOMOŚĆ PRZEDMIOTOWA I EPISTEMOLOGICZNA NAUCZYCIELA – REFLEKSYJNEGO PRAKTYKA Z PERSPEKTYWY POLSKIEJ GLOTTODYDAKTYKI - Karpińska-Musiał, Beata; Orchowska, Izabela (Neofilolog, 2019)
The following article concerns the issue of educating foreign language teachers to be reflective practitioners in the Polish academic context. A starting point for our discussion is the assumption that the process of academic FL teacher education should be directed at developing the student teacher’s disciplinary and epistemological awareness. The first part of the article is devoted to the concept of glottodidactics as a research area in Poland and to the evaluation of the usefulness of theories from the field of pedeutology for the formulation of a progressive model of teacher education. Next, we define the concepts of disciplinary and epistemological awareness of FL teachers, and confront them with the notion of reflective practice (Schön, 1983) and the paradigm of reflexive modernity (Beck, Giddens and Lash, 2009). Finally, we propose a preliminary model for developing both types of awareness in tertiary education, based on specific transpositions of glottodidactic knowledge into the skills needed in the field.